2020
DOI: 10.1111/jce.14575
|View full text |Cite
|
Sign up to set email alerts
|

Biophysical defects of an SCN5A V1667I mutation associated with epinephrine‐induced marked QT prolongation

Abstract: BackgroundThe epinephrine infusion test (EIT) typically induces marked QT prolongation in LQT1, but not LQT3, while the efficacy of β‐blocker therapy is established in LQT1, but not LQT3. We encountered an LQT3 family, with an SCN5A V1667I mutation, that exhibited epinephrine‐induced marked QT prolongation.MethodsWild‐type (WT) or V1667I‐SCN5A was transiently expressed into tsA‐201 cells, and whole‐cell sodium currents (INa) were recorded using patch‐clamp techniques. To mimic the effects of epinephrine, INa w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…Genomic DNA was extracted from peripheral blood lymphocytes, and target panel sequencing of 72 genes, including inherited arrhythmia syndrome‐related genes, was performed as previously described (Nakajima et al., 2020). Average read depth in analyzable target region was 197 in male and 244 in female sample.…”
Section: Methodsmentioning
confidence: 99%
“…Genomic DNA was extracted from peripheral blood lymphocytes, and target panel sequencing of 72 genes, including inherited arrhythmia syndrome‐related genes, was performed as previously described (Nakajima et al., 2020). Average read depth in analyzable target region was 197 in male and 244 in female sample.…”
Section: Methodsmentioning
confidence: 99%
“…These findings explain why cardiac events in patients with LQT1 are associated with physical activity and why β-blocker therapy has been established in LQT1 but not in LQT3. However, our own group and Chen et al reported LQT3 patients (with a SCN5A V1667I or V2016M mutation) exhibiting epinephrine-induced marked QT prolongation [ 11 , 46 ]. Electrophysiological experiments revealed that both mutant channels caused a gain-of-function by β-adrenergic stimulation.…”
Section: Lqts and Sqtsmentioning
confidence: 99%
“…The predominance of outward currents over inward currents at the epicardium in RV outflow tract (RVOT) during the early phase of ventricular APs, due to a loss-of-function of inward currents (such as I Na and I Ca ) or a gain-of-function of outward currents (such as I to and ATP-sensitive inward rectifier potassium currents [I K-ATP ]), can augment the AP notch ( Figure 1 A), thereby inducing coved-type ST segment elevations in the right precordial ECG leads ( Figure 1 B), and result in the development of fatal arrhythmias through a so-called phase 2 re-entry [ 3 , 112 ]. During the slower heart rate or lower physical activity, I to is augmented due to a recovery from inactivation and I Ca is decreased due to a reduced β-adrenergic stimulation, while I Na is minimally affected ( Figure 2 ) [ 11 , 113 , 114 ]. The decreased heart rate- and reduced β-adrenergic stimulation-induced predominance of outward currents over inward currents during the early phase of RVOT APs can explain why cardiac events of BrS tend to occur during sleep or at rest [ 3 , 112 ].…”
Section: J Wave Syndrome (Brs and Ers)mentioning
confidence: 99%
See 2 more Smart Citations